Papers of Frederick A. Edelsten (as filmed by AJCP) [M837] - Edelsten, Frederick A.; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Diary recording Edelsten's travels, 1867-1868. He arrived in Adelaide from England on 14 Oct. 1867 aboard the City of Adelaide. He travelled around the south-eastern district of South Australia and then made a return journey to Perth, travelling by ship from Adelaide to Albany and then by coach to Perth. In Aug. 1868 Edelsten returned to England via Albany and Ceylon, where he stayed a short while. The diary includes many observations on, and sketches of, Australian flora and fauna and photographs of Albany, Perth, Mt Eliza, scenes in the outback and the Edelsen warehouse in Adelaide. He describes in some detail the places visited and people encountered.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M837.
Also available online
Microfilm copy of originals held in private ownership.
Keywords: Edelsten, Frederick A. -- Diaries; City of Adelaide (Ship); Travelers -- Australia -- Diaries; South Australia -- Description and travel -- 1851-1900.; Western Australia -- Description and travel -- 1851-1900.